Locations of adenovirus genes required for the replication of adenovirus-associated virus. - Janik, J E (1981)
We have used DNA transfection to identify several regions of the adenovirus genome needed to induce replication of the defective parvovirus, adenovirus-associated virus (AAV). Previous studies have indicated that only early adenovirus functions are needed to aid the replication of AAV. In this report, we demonstrate that three restriction endonuclease fragments of adenovirus DNA are necessary for production of infectious AAV in 293-31 cells (an adenovirus type 5-transformed human embryonic kidney cell line). These fragments map from 28.5 to 29.4, 59.5 to 75.9, and 89.7 to 100 map units on the adenovirus type 2 genome and correspond to the locations of the VAI RNA gene, early region 2, and early region 4, respectively. The 293-31 cell line, which has been found to express early region 1A and 1B proteins, alone is incapable of supporting AAV replication or even AAV DNA synthesis. Additional experiments with adenovirus type 5 host range mutants (group I, hr1 and group II, hr7) indicate, however, that early region 1A provides an essential function(s) for AAV replication, whereas early region 1B probably does not.